The Reality of Musical Education among Kindergarten Teachers - Saza Hussen Rasul; Ali Najm Abdullah; Hemin Mohammed Abdullah (Zanco Journal of Humanity Sciences)
The Research aimed to identify the level of the Reality of Musical Education among Kindergarten Teachers in the city of Erbil in general and to know the differences in the Reality of Musical Education among Kindergarten Teachers according to the type of Kindergarten (Governmental and Non-Governmental) and years of service for Teachers (5 years and more and less). The Research Sample consisted of (366) Teachers in Kindergartens, and. A scale prepared by Researcher in (3) domains and (44) items, after validation and Reality. The scale was applied to the final sample, used the statistical bag (SPSS) in procedures, the results showed that levels of Musical Education Reality among kindergarten Teachers are generally unacceptable, just as the reality of musical education among non-governmental kindergarten teachers is high and acceptable compared to the reality of musical education among government kindergarten teachers, and that kindergarten teachers have years of service (5 years and Most) did not accept the reality of music education compared to kindergarten teachers, children with years of service (5 years and less).